Global Study Unveils Mind Mapping's Impact on Reading Skills: Studi Global Mengungkap Dampak Pemetaan Pikiran terhadap Kemampuan Membaca - Fitrawantono, Muhammad Rafly; astutik, yuli (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the effectiveness of the Mind Mapping Technique in improving reading comprehension among sixth-grade students in Sidoarjo, Indonesia. Using a pre-experimental design with pretest and posttest assessments, data from 20 students at Temu 2 Prambon Elementary School were analyzed using SPSS 26. Results show a significant improvement in post-test scores (average 68.5) compared to pre-test scores (average 49.5), indicating the positive impact of Mind Mapping on reading comprehension. These findings underscore the potential of Mind Mapping as an effective tool for educators to enhance students' reading skills, particularly in understanding descriptive content, offering valuable insights for educational practices in similar settings. Highliht: Effective Mind Mapping: Enhances sixth-grade reading comprehension. Quantitative Analysis: Validates method using SPSS. Educational Implications: Recommends Mind Mapping for elementary education. Keyword: Mind Mapping, Reading Comprehension, Elementary Education, Pre-experimental Design, SPSS Analysis